Efektivitas Minyak Zaitun dalam Mengatasi Pruritus pada Pasien Hemodialisis - Puspari, Titik; Haris, Fahni; Widiyanto, Purnomo (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
Chronic kidney disease (CKD) causes a progressive decline in renal function, necessitating lifelong hemodialysis (HD) as a replacement therapy. However, HD often leads to complications, including uremic pruritus, which negatively impacts patients' comfort, sleep quality, and overall well-being. Effective management strategies are essential to alleviate these symptoms. This study evaluates the efficacy of olive oil as a non-pharmacological intervention for managing uremic pruritus in HD patients. A case study approach was employed, involving four participants who applied olive oil (2–3 mL) three times daily for three consecutive days. Pre- and post-intervention assessments were conducted using the 5-D itch scale. Findings showed an average reduction in pruritus severity (n=4) by 3.5 (p < 0.001). Responses to the 5-D itch scale indicated improvements in skin hydration, wound healing, and sleep quality. Olive oil effectively reduced pruritus severity from severe to moderate, and from moderate to mild. Participants reported increased skin moisture, faster healing of scratch-induced lesions, reduced itching sensations, and enhanced sleep quality. Based on these findings, olive oil can be recommended as a safe and effective therapeutic option for CKD patients. Integrating olive oil application into nursing practice may help manage uremic pruritus and improve patient comfort by mitigating skin-related complications.